Perioperative Management of Buprenorphine: Solving the Conundrum - Quaye, Aurora Naa-Afoley (Pain Med, 2019)
OBJECTIVE: There is no consensus on the optimal perioperative management of patients on buprenorphine (BUP) for opioid use disorder (OUD). This article will review the available literature on BUP and the analgesic efficacy of BUP combined with full mu-opioid agonists and discuss the conflicting management strategies in the context of acute pain and our institution’s protocol for the periprocedural management of BUP. METHODS: We searched published data on BUP periprocedural management from inception through March 2018 without language restrictions. Study selection included publications reporting outcomes on perioperative pain management in OUD patients maintained on BUP. RESULTS: Our search resulted in four case reports supporting periprocedural discontinuation of BUP and two case series, one secondary observational study, one prospective matched cohort study, and four retrospective cohort studies supporting periprocedural continuation of BUP. No clinical trials were identified. CONCLUSIONS: Maintaining BUP perioperatively does not lead to worsened clinical outcomes. Patients can receive adequate pain control from mu-opioid agonists while maintained on BUP. Based upon available evidence, we recommend continuing BUP at a reduced dose when indicated to avoid withdrawal symptoms and to facilitate the analgesic efficacy of mu-opioid agonists administered in combination for acute postoperative pain.